Evaluación de la eficacia biológica y de la sensibilidad de Aedes aegypti a los insecticidas piretroides deltametrina y ciflutrina durante el brote del virus Zika en Kuna Yala, Panamá. - Cáceres, Lorenzo; Ayarza, Cipriano; Bernal, Damaris (Biomédica: Revista del Instituto Nacional de Salud, 2023)
Introduction. The development of resistance to insecticides in Aedes aegypti represents a major threat to public health. Surveillance and monitoring of the biological efficacy and sensibility of Aedes aegypti populations to insecticides is fundamental to prolong the useful life of insecticide molecules. Objective. To evaluate the biological efficacy of deltamethrin and cyfluthrin and sensibility to insecticides in Aedes aegypti during the zika epidemic outbreak in Kuna Yala, Panama. Methods and materials. We assessed the biological efficacy of deltamethrin and cyfluthrin, and sensibility in the strain Aedes aegypti Ustupo using bioassays standardized by the World Health Organization during the Zika epidemic outbreak in Kuna Yala, Panama. Results. In the bioassays with Aedes aegypti Ustupo, we observed a possible resistance to deltamethrin and cyfluthrin with a mortality rate of 95,3 and 94%, respectively. The obtained results registered low biological efficacy of deltamethrin and cyfluthrin with average percentages of mortality of 75 and 31.1% in the intradomicile, and 63,7 and 26.1% in the peridomicile. Conclusion. The results of this study represent a challenge for the National Aedes Control Program to care for and maintain the toxic effect of insecticides applied against Aedes populations. There is a need for the National Aedes Control Program to establish some guidelines about resistance assessment and resistant populations' geographic distribution to guarantee the sustainability of anti-vector interventions against Aedes populations.